2019
DOI: 10.1038/s41588-019-0395-x
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptome-wide association study of high-grade serous epithelial ovarian cancer identifies new susceptibility genes and splice variants

Abstract: We sought to identify susceptibility genes for high-grade serous ovarian cancer (HGSOC) by performing a transcriptome-wide association study (TWAS) of gene expression and splice junction usage in HGSOC-relevant tissue types (N = 2,169) and the largest GWAS available for HGSOC (N = 13,037 cases/40,941 controls). We identified 25 TWAS significant genes, 7 at the junction level only, including LRRC46 at 19q21.32, (P = 1 × 10−9), CHMP4C at 8q21 (P = 2 × 10−11), and a PRC1 junction at 15q26 (P = 7 × 10−9). In vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 61 publications
3
101
1
Order By: Relevance
“…For ovarian cancer, we identified 17 candidate susceptibility genes that were located within 1 Mb of a published lead variant associated at genome-wide significance with ovarian cancer risk (Supplementary Table 5; (23)). Six of these genes have also been reported in a previously published TWAS for ovarian cancer ( Supplementary Table 5; (11,12)). The 17 genes span 5 different genomic regions > 1 Mb apart.…”
Section: Candidate Breast Cancer and Ovarian Cancer Susceptibility Gementioning
confidence: 74%
See 2 more Smart Citations
“…For ovarian cancer, we identified 17 candidate susceptibility genes that were located within 1 Mb of a published lead variant associated at genome-wide significance with ovarian cancer risk (Supplementary Table 5; (23)). Six of these genes have also been reported in a previously published TWAS for ovarian cancer ( Supplementary Table 5; (11,12)). The 17 genes span 5 different genomic regions > 1 Mb apart.…”
Section: Candidate Breast Cancer and Ovarian Cancer Susceptibility Gementioning
confidence: 74%
“…In this study, we used the conditional and conjunctional FDR as a novel tool to systematically improve the power of breast cancer and ovarian cancer candidate susceptibility gene discovery in a PrediXcan-based TWAS. While gene expression prediction models based on multiple tissue types has been the more common approach to improving TWAS power (11,28), the conditional/conjunction FDR approach gains power through the incorporation of multiple related GWAS data sets into a TWAS analysis. We investigated the shared inherited genetic basis of these two cancer types by integrating normal and tumor tissue-specific transcriptomic data sets with largescale genome-wide association meta-analysis findings for susceptibility to breast cancer and ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated the colocalization status of a gene by calculating the posterior probability that the genetic and functional associations derived from (i) distinct causal SNPs (PP3), and (ii) a shared causal SNP (PP4) (24). Of the 177 significant features, 101 (57 unique genes) were considered as colocalized based on their high PP4 (> 0.8), in line with previous literature (25,26) ( Supplementary Table S3).…”
Section: Colocalizationmentioning
confidence: 96%
“…whether or not SNPs are eQTLs) [17][18][19][20] . Application of these methods to eQTL and GWAS data has shown that many genes have eQTLs that colocalize with GWAS loci [6][7][8][9][10] and/or exhibit significant cis-genetic correlations between their expression and trait [11][12][13][14][15][16][21][22][23][24][25][26][27][28] , while also showing that eQTLs as a whole are significantly enriched for disease heritability [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%